On liberal revolution - Gobetti, Piero, 1901-1926 (Italian literature and thought series., 2000)
This book is the first English-language edition of a collection of writings by one of Italy's most important radical liberals, Piero Gobetti (1901-1926). In thirty-five thought-provoking essays, Gobetti proposes an original and challenging notion of liberalism as a revolutionary theory of both the individual and social and political movements. His theory is of particular relevance in the wake of the collapse of Marxist socialism, as non-Western countries with nonliberal or antiliberal cultural and moral traditions confront the problems of transition toward democracy and liberalism. Gobetti's ideas continue to influence in important ways today's heated debates over the nature of liberalism. Gobetti was the first Italian scholar to identify "two Italys": one enlightened and modern though small and weak, the other premodern, traditional, and dominant. A witness to the seizure of power by the Fascists, Gobetti became convinced that Italy's hostility to liberalism could be overcome only with a cultural revolution. Endorsing a radical liberalism, he nevertheless believed that the Communists, led by Antonio Gramsci, could play a crucial role in democratizing Italy by helping to develop a secular culture. For a liberal state to subsist and grow, Gobetti argued, there must first be a transformation of both the economic structure and the legal and moral culture of the society